2017
DOI: 10.1186/s13034-017-0152-9
|View full text |Cite
|
Sign up to set email alerts
|

Identifying cross-cultural variations in psychostimulant use for attention deficit hyperactivity disorder using linked data

Abstract: BackgroundTo validate the association between country-of-birth and disparities in the stimulant use for ADHD among individuals in Western Australia.MethodsUsing linked data, a population-based retrospective cohort of individuals admitted to hospital before age 25 years was followed through to identify having stimulants for ADHD in 2003–2007. Multivariate logistic and linear regressions were used to characterise associations between stimulants and country-of-birth, geographical remoteness and socioeconomic stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Further research examining the association between household size and mental health outcomes is needed. In addition, our finding of an inverse association between stimulant dispensing and the proportion of the population that are not Canadian citizens is similar to prior research demonstrating less use of these drugs among immigrants [ 60 63 ]. Whether this reflects less access to diagnostic testing and treatment, implicit bias on the part of health-care providers or teachers, cultural responses to health and illness or a combination of the above requires further study.…”
Section: Discussionsupporting
confidence: 88%
“…Further research examining the association between household size and mental health outcomes is needed. In addition, our finding of an inverse association between stimulant dispensing and the proportion of the population that are not Canadian citizens is similar to prior research demonstrating less use of these drugs among immigrants [ 60 63 ]. Whether this reflects less access to diagnostic testing and treatment, implicit bias on the part of health-care providers or teachers, cultural responses to health and illness or a combination of the above requires further study.…”
Section: Discussionsupporting
confidence: 88%
“…Treatment adherence is defined by the World Health Organization as ''the degree to which the person's behavior corresponds with the agreed recommendations from a health care provider'' (Dobbels, van Damme-Lombaert, Vanhaecke, & De Geest, 2005). Several studies in this field have concluded that after consulting a mental health care service, ethnic minority children were less likely to use ADHD-related medications after their diagnosis and had a higher drop-out rate from psychological or psychopharmacological treatment (e.g., Coker et al, 2016;dosReis et al, 2003;Ghosh et al, 2017;Ji et al, 2018;Morgan et al, 2013). For instance, Cummings et al (2017) have recently reported that African American and Hispanic youth (6-12 years) were more likely than White youth to receive combined treatment for ADHD but were also more likely to discontinue medication and disengage from treatment (Cummings et al, 2017).…”
Section: Cultural Diversity In Treatment Variablesmentioning
confidence: 99%
“…While the two studies cannot be compared directly, both of them suggested a lower initiation of ADHD medication within the immigrant population. Immigrants in general might be prone to underutilizing psychiatric health care ( 41–44 ), but other factors such as cultural beliefs and attitudes toward behavioral symptoms and medication of ADHD ( 45 , 46 ), health literacy ( 47 ), language problems, or occupation might also contribute to less frequent medication initiation. A study among children, who were born between 1995 and 2004 in Sweden, found that children who had only foreign-born parents were less likely to use medication compared with children who had at least one Swedish-born parent, suggesting that ADHD medication use might be influenced by cultural factors ( 46 ).…”
Section: Discussionmentioning
confidence: 99%